2015
DOI: 10.1186/s12885-015-1220-2
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous deletions of UGT2B17 modifies effects of smoking on TP53-mutations and relapse of head and neck carcinoma

Abstract: BackgroundSmoking induces oncogenic TP53-mutations in head and neck squamous cell carcinomas (HNSCCs). Disruptive mutations of TP53-gene and expression of p16 protein [p16 (+)] in tumor tissue associate with worse and better prognosis, respectively. UDP-glucuronosyltransferase 2 family, polypeptide B17 (UGT2B17) detoxifies smoking-related metabolites. Differences among ethnic groups in UGT2B17 are extremely high. Homozygous deletions of UGT2B17 gene (UGT2B17-deletion) are a common copy number variant (CNV) amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
0
14
1
Order By: Relevance
“…More specific definitions for nonsmoking varied from "<100 cigarettes in their lifetime" to "…smoked less than 10 pack-years prior to the surgical resection of HNSCC." 67,71 For nondrinking, the definitions ranged from never having "consumed at least 1 drink/week continuously for at least 6 months" to "drinking less than five units of sake (=140 g alcohol) per day for 1 year" (Table 1). 37,52 3.3 | Meta-analysis on molecular parameters HPV, p16 overexpression, and TP53 mutations Twelve studies detected HPV presence using at least two identification techniques in HNSCC of nonsmokers, and Figure 3A,B).…”
Section: Assessment Of Study Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…More specific definitions for nonsmoking varied from "<100 cigarettes in their lifetime" to "…smoked less than 10 pack-years prior to the surgical resection of HNSCC." 67,71 For nondrinking, the definitions ranged from never having "consumed at least 1 drink/week continuously for at least 6 months" to "drinking less than five units of sake (=140 g alcohol) per day for 1 year" (Table 1). 37,52 3.3 | Meta-analysis on molecular parameters HPV, p16 overexpression, and TP53 mutations Twelve studies detected HPV presence using at least two identification techniques in HNSCC of nonsmokers, and Figure 3A,B).…”
Section: Assessment Of Study Qualitymentioning
confidence: 99%
“…52,81,84,88 In addition, mutations in the abovementioned studies were reported in exons 4 to 8 and 10, repeatedly at a CpG site, and were less common in nasopharyngeal squamous cell carcinoma and HPVpositive OPSCC. 52,71,[79][80][81]84…”
Section: Assessment Of Study Qualitymentioning
confidence: 99%
“…Besides additional genetic variants in the UGT2B17 gene locus, those affecting expression of the FOXA1 transcription factor might also be important. This knowledge will help understand the biologic impact of this enzyme in health and diseases, namely, on the endocrine system (Juul et al, 2009;Mouritsen et al, 2018), osteoporosis (Yang et al, 2008), carcinogen exposure (Chen et al, 2010), head and neck cancer (Mafune et al, 2015), prostate cancer (Kpoghomou et al, 2013;Li et al, 2016), chronic lymphocytic leukemia (Gruber et al, 2013;Bhoi et al, 2016), pediatric cancer (Ishimaru et al, 2017), and on inactivation of antineoplastic and other therapeutic agents (Kang et al, 2010;Sun et al, 2010;Wang et al, 2012).…”
Section: Specific Quantification Of Ugt2b17mentioning
confidence: 99%
“…Smoking was associated with increasing risk of developed benign salivary gland tumor 20 , however, the relation of smoking and malignant salivary gland cancer still under debated 21 , and seen probably influenced male only 16 , 21 . Smoking induced oncogenic TP-53 mutation 22 , which significantly associated higher relapse rate 24 and reduced survival 23 , in head and neck squamous cell carcinoma. TP53 gene alternation also associated with a poor outcome in salivary gland cancer 25 .…”
Section: Discussionmentioning
confidence: 99%